Vegetation response to changes in climate across different climate zones in China - Hanyu Ren; Zhongming Wen; Yangyang Liu; Ziqi Lin; Peidong Han; Haijing Shi; Zhenqian Wang; Tongxuan Su (Ecological Indicators, 2023)
Vegetation growth is sensitive to climate change. The complex climate types of China pose great challenges to the sustainable management of vegetation on global change. Therefore, this study used Enhanced Vegetation Index (EVI) as an indicator to explore the spatiotemporal dynamics of vegetation and their driving factors in different climatic zones of China to provide theoretical support for sustainable vegetation management in different climate zones in the future. The results showed that vegetation exhibited considerable clustering patterns in the country, with high and low values concentrated in the eastern and western regions, respectively. From 2001 to 2020, both at regional and pixel scales, vegetation in China showed a significant greening trend. EVI displayed a noticeable increase within temperate and subtropical areas. The only exception is observed in the eastern coastal area of the North China Plain and Yangtze River Delta region, which experienced evident degradation trend. During this period, China's climate showed an overall trend towards warming and humidification with drying trends observed mainly over the western regions. The impact of climate changes resulted in EVI dynamics that vary over time and space. The vegetation change in China was mainly derived by changes in precipitation and radiation rather than temperature, especially in temperate and subfrigid regions. Precipitation was the main driving factor for vegetation greening in tropical and temperate regions, while radiation and temperature were the dominant climate factor for vegetation greening in subfrigid and subtropical regions, respectively. When precipitation was no longer a limiting factor for vegetation growth, the effect of temperature or radiation increases. In addition, the positive impact of precipitation on plant growth in temperate regions was much greater than that of radiation and temperature, and this difference was much greater than in tropical, subtropical, and subfrigid regions.